2011
DOI: 10.1179/1743132811y.0000000013
|View full text |Cite
|
Sign up to set email alerts
|

Clipping surgery for aneurysmal subarachnoid hemorrhage in patients aged 75 years or older

Abstract: Object: The incidence rate of aneurysmal subarachnoid hemorrhage (SAH) in the elderly is increasing. Although endovascular coiling has become a major form of treatment for SAH in elderly patients, not all ruptured aneurysms can be managed with an endovascular approach.Conventional surgical clipping still plays an important role in SAH treatment. The present study was performed to assess the outcome in patients older than 75 years of age in whom ruptured aneurysms were treated by clipping surgery. Results: A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…Of two articles by Horiuchi et al, the latest one with more cases was excluded, because it investigated cases 80 years of age or older, while the older one investigated cases 75 years of age or older. 11 , 12) Two articles by Hamada et al had no overlap of cases, and both articles were included. 13 , 14) Two articles by Asano et al were from different institutions and had no overlap of cases; both were therefore included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of two articles by Horiuchi et al, the latest one with more cases was excluded, because it investigated cases 80 years of age or older, while the older one investigated cases 75 years of age or older. 11 , 12) Two articles by Hamada et al had no overlap of cases, and both articles were included. 13 , 14) Two articles by Asano et al were from different institutions and had no overlap of cases; both were therefore included.…”
Section: Resultsmentioning
confidence: 99%
“…A comparative investigation with other time-spans under age 75 was performed in three studies, 5 , 17 , 18) and a comparative investigation between several time-spans of 75 or 80 years of age or older was performed in three studies. 4 , 11 , 17) One article investigated mainly a comparison among different time spans, while the data for the patients over 75 years of age included outcome only. 17) Of 12 articles, eight studies were performed in Japan, and the other four studies were performed in several developed countries.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Horiuchi et al . [5] suggested that advanced age was not a risk factor for a poor outcome of clipping surgery in elderly patients, and Karamanakos et al . [8] suggested that integration of coil treatment in clinical practice has not improved the overall outcome of SAH in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies were based on observational ones of the surgical group without any control group,3 or historical control groups,4 or case-control studies which compared between the elderly 5 6. To date, there has been no study which compared the elderly patients of aSAH who received clip/coil treatment with those who did not.…”
Section: Discussionmentioning
confidence: 99%